Survey for major grapevine viruses in commercial vineyards of Northwestern Argentina - Rivadeneira, Monica; Galvan, Marta Zulema; Aban, Marina Paola; Semke, Rosa Elena; Rivadeneira, Josefina; Lanza Volpe, Melisa; Gomez Talquenca, Gonzalo (MDPI, 2022)
This study aimed to survey the occurrence of eight grapevine viruses in commercial vine yards located in the Calchaquíes Valleys in the northwest region of Argentina. A total of 103 samples of mature canes of vines showing either none or some viral-like symptoms were randomly collected. The samples were tested by RT-PCR/PCR-based assays for the screening of the following viruses: Grapevine fanleaf virus (GFLV), Grapevine leafroll-associated viruses (GLRaV-1, -2, -3, -4), Grapevine virus A (GVA), Grapevine rupestris stem pitting-associated viruses (GRSPaV), and Grapevine red blotch virus (GRBV). Sixty percent of the analyzed samples showed infection with some of the analyzed viruses, except GRBV. GLRaV-3 and GFLV were the most frequent viruses, present in 34% and 21% of the pos itive samples, respectively. This study represents the first survey report of the presence of grapevine viruses in the region of the Calchaquíes Valleys and contributes to the knowledge to maintain the sanitary status of commercial vineyards in Argentina.